The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.euf.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamics Useless in Female Stress Urinary Incontinence? Time for Some Sense—A European Expert Consensus

Abstract: A group of experts were worried that, even though the cause of incontinence varies, doctors seem to be skipping a diagnostic test called urodynamics (UDS) in some patients and just providing treatment-even surgery-without knowing exactly what is wrong. These experts analysed the situation in detail and reached agreement that UDS testing should not be skipped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…The main area of debate is that many clinicians believe that UDS is indicated in refractory OAB and only when initial therapy fails and it should be performed prior to any surgical intervention including minimally invasive procedures, such as sacral neuromodulation or onabotulinumtoxinA injection. They support this opinion with studies that showed that UDS is an invasive expensive tool, time consuming, and does not influence the initial management strategies [36,37].…”
Section: Oabmentioning
confidence: 70%
See 1 more Smart Citation
“…The main area of debate is that many clinicians believe that UDS is indicated in refractory OAB and only when initial therapy fails and it should be performed prior to any surgical intervention including minimally invasive procedures, such as sacral neuromodulation or onabotulinumtoxinA injection. They support this opinion with studies that showed that UDS is an invasive expensive tool, time consuming, and does not influence the initial management strategies [36,37].…”
Section: Oabmentioning
confidence: 70%
“…A recent expert consensus viewpoint on the value of UDS in female SUI was achieved in a review article that has been published recently. They concluded that extensive experience and observational studies have shown the danger of empiric management for SUI and strongly supported the value of UDS for the assessment of female SUI [36].…”
Section: Complicated Vs Uncomplicated Suimentioning
confidence: 91%
“…These recommendations, and others [14,15], were strongly influenced by two randomized controlled trials (RCTs) in women with P-SUI published in 2012the ValUE and VUSIS-II studies [16][17][18] which concluded that UDS findings were not useful in this setting. However, both of these studies have sparked considerable controversy and criticism of their design and conclusions, as summarized in a recent European consensus article [19]. 1 The first evident issue is the lack of a standardized definition of uncomplicated SUI.…”
Section: Contentsmentioning
confidence: 99%
“…A much more likely hypothesis is that, in 34 % of non-P-SUI women, UDS was not seen as a necessary preoperative tool even in these more complex cases, mirroring the findings of the Dutch survey. It is important to recognize not only that the great majority of cases of SUI are not uncomplicated, but that UDS has been shown to have intrinsically greater benefit in complex cases than in P-SUI [23,24] and that a wide range of prospective and retrospective studies have demonstrated the value of UDS in diverse SUI patient cohorts [19].…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation